Virologic suppression among HIV-infected US Air Force members in a highly-structured programme with free access to care. (November 2015) - Matthews, PE; Le, T; Delmar, J; Okulicz, JF
Summary: The United States Air Force HIV programme has several features that may enhance antiretroviral therapy outcomes, including free access to healthcare and mandatory clinical visits every six months at a single centre. We evaluated viral load suppression (<50 copies/ml) after 12 months of initial antiretroviral therapy, with extension to 18 and 24 months. Active duty Air Force members were categorised by year of antiretroviral therapy initiation: 2000–2005 (n = 95, 36.1%) and 2006–2011 (n = 168, 63.9%). The median months from HIV diagnosis to initial antiretroviral therapy were shorter in the 2000–2005 group (2.4, IQR 1.2–5.9) compared with the 2006–2011 group (12.6, IQR 2.6–29.0; p < 0.001). Viral load suppression was greater in the 2006–2011 group compared with the 2000–2005 group at 12 months (93.2% versus 78.6%, p = 0.002) and 18 months (91.8% versus 80.3%, p = 0.03), and trended higher at 24 months (90.8% versus 82.5%; p = 0.15). Factors associated with viral load suppression at 12 months in multivariate models included antiretroviral therapy initiation during 2006–2011 (OR 5.22, 95% CI 1.50–18.18) and CD4 count at antiretroviral therapy initiation (OR 2.29, 95% CI 1.19–14.43 per 100 cells/µl increase). Structured programmes that minimise traditional barriers to care combined with the use of contemporary antiretroviral therapy regimens can achieve clinic-wide viral load suppression in >90% of patients.